OPTIMALISASI INSTAGRAM SEBAGAI MEDIA KAMPANYE POLITIK: STUDI KASUS PUTRA NABABAN DALAM MENINGKATKAN KETERLIBATAN DAN DUKUNGAN PEMILIH DI ERA DIGITAL - Angelia Stephanie Vadia; Bintang Aura Mayesa Putri; Fitto Meizan; Ismoyo Sekar Prastin; Mahesha Suryo Megantara; Restu Rahmawati (Cahaya Ilmu Bangsa, 2024)
This study analyzes Putra Nababan's political campaign strategy for the 2024 Legislative Election, focusing on the use of social media to increase vote count. Social media platforms like Facebook, Instagram, and Twitter provide opportunities for legislative candidates to directly interact with voters and effectively convey their political messages. This research aims to evaluate the extent to which social media use influences voter decisions, particularly among the younger generation. Data was collected through an analysis of Putra Nababan's social media campaign activities and surveys of voters regarding their perceptions of political content on these platforms. The results show that campaign strategies involving visual content, direct interaction, and paid advertisements on social media significantly boost voter engagement and participation. These findings highlight the crucial role of social media in modern political campaigns, especially among digitally connected younger voters. This research offers insights for other legislative candidates on the importance of leveraging digital technology in political campaigns to achieve optimal results.